Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas 3B SDN 37 Cakranegara Tahun 2023 - Afifaturrahmi, Afifaturrahmi; Hidayati, Nurlia; Adinda, Dayita Wahyu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research is motivated by the learning outcomes of class 3B students at SDN 37 Cakranegara which are still below the KKM. For this reason, researchers apply the Problem Based Learning learning model with the aim of improving student learning outcomes. Participants in this research were class 3b students at SDN 37 Cakranegara in 2023. This research is classroom action research using the Kemmis and Mc model. Taggart. The research instrument is in the form of student and teacher observation sheets to see the achievements of implementing the Problem Based Learning model as well as evaluation sheets to measure student learning outcomes. The research results show that students' learning mastery is increasing at each stage of the research cycle. In cycle I, student learning completion was 45%, in cycle II 63%, and in cycle III it reached 95%. Thus, the Problem Based Learning learning model can be applied as a learning model that can improve the learning outcomes of class 3b students at SDN 37 Cakranegara.